OVERSHADOWING AND ACQUISITION IN HUMAN CONTINGENCY JUDGMENTS - Martín, Ignacio; Arnau Gras, Jaume; De la Fuente Solana, Emilia Inmaculada; Iglesias Parro, Sergio (Anales de Psicología / Annals of Psychology, 2001)
This article studies the impact of the competition cues and the acquisition in human contingency judgements. For that matter we will use an overshadowing task similar to Gluck and Bower`s where it studies the judgments in different moments of the experiment task ( Experiments 1 and 2). In this way ( Experiments 3 and 4) studies if the process of judgments acquisition is a phenomenon caused by the repetition of the measuring or if it is caused independentlyof the times in which subjects make judgments. We also study the fitting of the empirical dates with simulate dates, starting from the principal normative models propose in this area. The results of overshadowing show a significant effect of the competition cues about the subject´s judgments. About the acquisition we don´t find a significant effect of this variable. Finally, the results of thecomparisons between empirical-simulated judgments showthat the model which produces the best fitting is Bayer´sRule.